Teaching green content in Berlin VET schools - Kress, Hannelore [Verfasser]; Wittrock, Christian [Verfasser] (My University, 2024)
„The increased integration of sustainability-relevant aspects along the regional education ministries (Kultusministerkonferenz) framework in the various occupational profiles during training since 2021 is a central concern and challenge also for VET schools in Berlin.“ (authors‘ abstract; BIBB-Doku)
Keywords: S 3.1 Berufsbildende Schulen; S 2.2.3.1 Rahmenlehrpläne; 370; Berufsbildendes Schulwesen; Nachhaltige Entwicklung; Rahmenlehrplan; Berlin